Supporting Informed Decision Making in Prevention of Prostate Cancer - Martins, Constantino; Silva, Ana Rita; Martins, Carlos; Marreiros, Goreti (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
Identifying and making the correct decision on the best health treatment or screening test option can become a difficult task. Therefore is important that the patients get all types of information appropriate to manage their health. Decision aids can be very useful when there is more than one reasonable option about a treatment or uncertain associated with screening tests. The decision aids tools help people to understand their clinical condition, through the description of the different options available. The purpose of this paper is to present the project “Supporting Informed Decision Making In Prevention of Prostate Cancer” (SIDEMP). This project is focused on the creation of a Web-based decision platform specifically directed to screening prostate cancer, that will support the patient in the process of making an informed decision